Implementation of pediatric nursing documentation quality audit : a mixed method study - Neneng Sundari; Suni Hariati; Rini Rachmawaty (Pediomaternal Nursing Journal, 2026)
Introduction: Pediatric nursing records are riskier due to limited patient communication, requiring audits to improve care and detect standard deviations. Although nursing documentation has been widely studied, most research has focused on general barriers such as workload, time constraints, staffing shortages, lack of appropriate formats, and inadequate perceptions of the discharge planning process. However, the implementation of nursing documentation in pediatric units, which have their own unique complexities, and research examining documentation practices within the clinical, developmental, and safety complexities remains very limited. Objective: This study aims to identify the implementation of quality audits of pediatric nursing documentation. Methods: This study employed a concurrent mixed-method design. Qualitative data were obtained through semi-structured interviews with eight participants selected purposively and were analyzed using thematic analysis with the assistance of Open Code software version 4.2. Meanwhile, a total of 260 medical records were selected using accidental sampling and evaluated using the D-Catch instrument with descriptive statistical analysis. Results: The study findings indicated that none of the three hospitals had policies related to the implementation of nursing documentation quality audits. A total of 260 medical records were audited of the 75 medical records at the National General Hospital, 82.7% were categorized as complete in almost all aspects of the medical record structure; of the 83 medical records at the Regional General Hospital, 43.4% were categorized as complete; and of the 102 medical records at the Teaching Hospital, only 17.6% were categorized as partially complete. The results of interviews with eight participants identified six main themes: (1) auditors' perceptions of the quality audit of nursing documentation, (2) audit planning, (3) audit implementation, (4) audit result evaluation, (5) audit result control, and (6) improvement of audit results. Conclusion: The lack of director-endorsed policies in hospitals limits the implementation of pediatric nursing documentation audits. Differences in documentation accuracy emphasize the need for auditors to possess strong comprehension and conduct thorough planning to improve nursing care quality efficiently. Keywords: nursing audit; nursing documentation; pediatric nursing